Air-conditioning in New Zealand: power and policy. Issue 1 (12th January 2022) - Byrd, Hugh; Matthewman, Steve; Rasheed, Eziaku
Policies, codes, standards and voluntary 'green' assessments have exacerbated cooling demand in New Zealand's commercial buildings. Building codes allow designs to use single glazing on the facade, voluntary 'green' criteria are not higher than the legal minimum in the code and inexpensive energy for commercial buildings all contribute to an increasing use of air-conditioning. Legal standards for the energy efficiency of the building envelope of commercial buildings have not significantly changed in over a quarter of a century and, over much of the same time, the cost of electricity (the predominant form of energy in New Zealand used to heat and cool buildings) has decreased for commercial buildings. These factors have led to an increased dependency on air-conditioning in commercial buildings. This increase in energy demand is unnecessary and can be reduced through policies, codes, and standards that reduce solar gain and use mixed-mode ventilation. The reduction in air-conditioning demand will improve energy security and reduce greenhouse gas emissions. Policy relevance: Inaction by successive governments (influenced by industries and lobby groups) has resulted in an energy culture in New Zealand that has moved air-conditioning from being a luxury to a dependency. The presented analysis makes a case for improving building standards to reduce commercial buildings' dependency on air-conditioning. New requirements could reduce energy demand by specifying a maximum energy allowed for cooling and a set of practical measures ( e.g . the use of natural ventilation, reduction of solar gain by the use of shading, consideration of orientation, maximum amounts of glazing in facades and higher performance specifications for glazing).